Pengaruh Komitmen Profesional pada Kepuasan Kerja Dengan Motivasi Sebagai Variabel Moderasi - Prawira, I Komang Egar; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi, 2018)
The purpose of this study was to examine the effect of professional commitment on job satisfaction with motivation as a moderating variable. This research was conducted at tax consultant office (KKP) in Denpasar area. Samples taken as many as 81 respondents by using purposive sampling method. Data collection was done by distributing questionnaires. The analysis technique used is with Moderated Regression Analysis (MRA). Based on the analysis results found that professional commitment has a positive and significant impact on job satisfaction at the Tax Consultant Office in Denpasar. These findings indicate that the higher the professional commitment the job satisfaction will increase, in addition the results of this study indicate that the role of motivation in professional commitment is strengthening, which means the implementation of professional commitment is better accompanied by the application of motivation together will be able to improve job satisfaction at the Tax Consultant Office in Denpasar. Keywords : professional commitment, job satisfaction, motivation.